Men's roles in care seeking for maternal and newborn health: a qualitative study applying the three delays model to male involvement in Morogoro Region, Tanzania - Jesse A. Greenspan; Joy J. Chebet; Rose Mpembeni; Idda Mosha; Maurus Mpunga; Peter J. Winch; Japhet Killewo; Abdullah H. Baqui; Shannon A. McMahon (BMC, 2019)
Abstract Background Increasing the utilization of facility-based care for women and newborns in low-resource settings can reduce maternal and newborn morbidity and mortality. Men influence whether women and newborns receive care because they often control financial resources and household decisions. This influence can have negative effects if men misjudge or ignore danger signs or are unwilling or unable to pay for care. Men can also positively affect their families' health by helping plan for delivery, supplementing women's knowledge about danger signs, and supporting the use of facility-based care. Because of these positive implications, researchers have called for increased male involvement in maternal and newborn health. However, data gathered directly from men to inform programs are lacking. Methods This study draws on in-depth interviews with 27 men in Morogoro Region, Tanzania whose partners delivered in the previous 14 months. Debriefings took place throughout data collection. Interview transcripts were analyzed inductively to identify relevant themes and devise an analysis questionnaire, subsequently applied deductively to all transcripts. Results Study findings add a partner-focused dimension to the three delays model of maternal care seeking. Men in the study often, though not universally, described facilitating access to care for women and newborns at each point along this care-seeking continuum (deciding to seek care, reaching a facility, and receiving care). Specifically, men reported taking ownership of their role as decision makers and described themselves as supportive of facility-based care. Men described arranging transport and accompanying their partners to facilities, especially for non-routine care. Men also discussed purchasing supplies and medications, acting as patient advocates, and registering complaints about health services. In addition, men described barriers to their involvement including a lack of knowledge, the need to focus on income-generating activities, the cost of care, and policies limiting male involvement at facilities. Conclusion Men can leverage their influence over household resources and decision making to facilitate care seeking and navigate challenges accessing care for women and newborns. Examining these findings from men and understanding the barriers they face can help inform interventions that encourage men to be positively and proactively involved in maternal and newborn health.